Decision Supporting System of Granting Loans with Binary Logistic Regression - Samsul Pahmi; Ade Hudiana; Lesri; Santi Laswati Suryadi; Lucas Cramer; Bahadir Ozsut (Nusa Putra University, 2021)
This research aims to identify the existing problems on the Koperasi Karya Usaha Mandiri as skim credit for poor families by granting credit in groups. The issue raised, namely the influence of Decision Supporting System of Granting Loans against credit jam. This research is a type of quantitative research which uses 8 independent variables and 1 dependent variable. Method of data collection in this research is the observation, interviews, literature studies and documentation. This research method uses Binary Logistic Regression to analyze the determination decision granting loans to prospective members and cause bottlenecks in financing micro-credits in Koperasi Karya Usaha Mandiri Syariah.